Software educacional: nematelmintos de aquisição passiva - Grincevicius, Tatiana Damasceno (2015)
The standard teaching method is based on the transmission of knowledge. Here, the teacher serves as subject matter expert and the student as an observer. However, this method no longer fits well with the current training needs of health professionals. A significant improvement can be realized when the teacher encourages maximum student motivation to awakening in them the quest for knowledge during the development of new skills and abilities. In this context, educational software should be included with the improved learning strategy. Interaction between science, technology and social knowledge are an essential aspect of preventing the transmission of human parasitic infections in school. Object: The main objective of this project is to evaluate and develop educational software utilizing Helminth parasitological images to interactively illustrate the passive transmission of roundworms. This can be useful to teachers, professionals and graduate students from various health disciplines to understand and identify these worms as well as for use by professionals in their practice. Methodology: The software was built using Multimedia Flash and a database of images. This enabled the creation of animations and simulations in vector language, resulting in smaller files that can be made available through the web or provided on other storage media. The final product was evaluated by medical students. Results: The software has been completed and has been favorably evaluated by students of medicine (n = 97) of the Faculty of Ciências Médicas e da Saúde da PUC/SP. Their tests compared results before use of the software with results obtained after using the software. A consistent growth of knowledge was demonstrated either by self-assessment or closed objective questions. Conclusion: The results obtained allow us to conclude that the software is of great educational interest and should be useful to students, teachers and professionals in the health field